Sistem Pemilihan Vendor Instalasi Menggunakan Metode Analytical Hierarchy Process dan Simple Additive Weighting - Hauzan, Muhammad; Aris Tantowi, Akhmad; Achmad Birowo (Institut Informatika Dan Bisnis Darmajaya, 2025)
Telecommunication companies in carrying out network infrastructure development cannot be separated from the existence of cooperative relationships with vendors. Considering the importance of vendor selection, an information system in the form of an application is needed to make vendor selection can be done systematically and structured. This study aims to facilitate employees in selecting vendors, analyze employee knowledge in the vendor selection process, and implement a decision support system using a combination of the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. The research will be carried out in several research stages. Where, data collection is carried out through in-depth interviews, observations, and literature studies. This study involves the stages of identifying key criteria in vendor selection and determining the types of attributes of each criterion according to the SAW method, formulating a pairwise comparison matrix to determine the weight of the criteria according to the AHP formula, then calculating the best vendor ranking based on the results of the SAW calculation. The results of this study are to facilitate employees in implementing network infrastructure installation services, a support system application has been created and designed that can assist in decision making when selecting vendors. Vendor selection data has been implemented through a strategically computed system, which is able to store and manage data well so as to increase its security.